PROFESIONALITAS APARAT DALAM PELAYANAN PUBLIK DI DESA PANTUNGO. KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Abdurrahman Idji, Rusly (STISIPOL Mujahidin Buol, 2024)
This study aims to obtain an overview of how the Professionalism of Apparatus in Public Service in Pantungo Village, Telaga Biru District, Regency The research method uses a qualitative type using a descriptive approach. Data collection techniques are carried out through interviews, observations and documentation. The results of the study show that the professionalism of the Pantungo Village officials related to the knowledge of the lack of competence of employees in providing public services is optimal, namely, the educational background of the apparatus and the level of understanding of the apparatus towards the work procedures are appropriate, while the professionalism of the Pantungo Village officials related to the Skill of employees in operating computer technology in services